2015
DOI: 10.4103/2231-0762.164790
|View full text |Cite
|
Sign up to set email alerts
|

DMFT index assessment, plaque pH, and microbiological analysis in children with special health care needs, India

Abstract: Aim:To assess the DMFT index of children with Special Health Care Needs (SHCN) in Navi Mumbai. To correlate the DMFT index with Streptococcus mutans count in the supragingival bacterial biofilm and with plaque pH.Materials and Methods:Dental examination of 158 patients aged 5–18 years was conducted to determine the DMFT/dmft index. Supragingival plaque samples were collected from the buccal surfaces of all teeth. The samples were inoculated in mitis salivarius bacitracin agar medium and incubated at 37°C for 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Unfortunately, care of oral health is one of the major unattended health needs of the disabled children. 19 Keeping the above facts in mind and so such is conducted in this part of Rajasthan state. The present study was conducted with the aim to assess the prevalence of dental caries and periodontal diseases among deaf & mute children attending various special schools in Jaipur city.…”
Section: Introductionmentioning
confidence: 97%
“…Unfortunately, care of oral health is one of the major unattended health needs of the disabled children. 19 Keeping the above facts in mind and so such is conducted in this part of Rajasthan state. The present study was conducted with the aim to assess the prevalence of dental caries and periodontal diseases among deaf & mute children attending various special schools in Jaipur city.…”
Section: Introductionmentioning
confidence: 97%
“…However contrary to our study,Subramaniyam et al and Katge et al found higher microbial load in the biofilm and poorer periodontal health in children with special needs and a statistically significant difference with gender. (Shivakumar et al, 2018) (Subramaniam and Gupta, 2013; Katge et al, 2015) The reason for this can be attributed to the fact that the oral hygiene maintenance of special children depends more on the maintenance procedures carried out by the caregivers than on the individual (Tesini and Fenton, 1994;Oredugba and Akindayomi, 2008). Age group of patients with special needs does not appear to be a major determinant for oral hygiene and caries incidence.…”
Section: Resultsmentioning
confidence: 99%
“…Four hundred young permanent first molars in 100 patients between 8 years and 10 years and who had all the four permanent molars erupted were screened in the institution and pit and fissure morphology were examined and recorded (Table 1). Young permanent first molars were examined using dental caries diagnostic index, DMFSM1 index per WHO guidelines (2013), 13 and pit and fissure morphology index (Symons 1996). 14…”
Section: Data Collectionmentioning
confidence: 99%